Approaching Hysteria through an Irigararian Perspective in Fay Weldon’s Praxis - Omar Mohammed Abdullah (European Scientific Journal, ESJ, 2016)
Hysteria is read as ‘the female malady’, a disease or sickness women suffer from. This reading could be one among other such readings that construe hysteria as a transgressive force by which women achieve or regain some lost desire. Luce Irigaray considers hysteria as a non-verbal language employed as a form of protest against patriarchal law which is instrumental in bequeathing hysteric symptoms to women. Constant fear, disturbed sleep, marginalization, trauma … etc., are products of patriarchy which manifest in women. The heroine in Fay Weldon’s Praxis also suffers similar symptoms. Irigaray’s reading of hysteria with sub-concepts of Mimicry and Masquerade will help to explore and reveal hysteria as a transgressive means by which women fight for their existence and attain their desires. This reading is applied to Weldon’s novel to reveal how the protagonist managed to construct an identity she strived for through hysteria.